Strategic Management of Character Education: A Holistic Model for Fostering Socio-Religious Attitudes in an Islamic Elementary School in Indonesia - Dian; Dianing Banyu Asih; Elis Karwati Sri Mulyani; Silviana Putri; Muhammad Iksan Fahmi Nusyeha; Nadira Salsabila (Badan Litbang dan Diklat Kementerian Agama RI, 2025)
The decline in moral values and religious internalization among elementary school students necessitates effective character education management. This study aims to describe the strategic management of character education in shaping students' socio-religious attitudes at SD Assalam Bandung, an Islamic elementary school in Indonesia. Using a qualitative case study approach, data were collected through observation, in-depth interviews, and document analysis. The results reveal a three-phase strategic management model: (1) strategic formulation through a vision-based